Reclamation intensifies the positive effects of warming on N2O emission in an alpine meadow - Li, Zheng; Li, Yan; Hu, Guozheng; Wu, Hongbao; Liang, Yan; Yan, Jun; He, Shicheng; Ganjurjav, Hasbagan; Gao, Qingzhu (Frontiers in Plant Science, 2023)
Climatic warming can alter grassland nitrous oxide (N2O) emissions due to soil property alterations. However, how the reclamation affect grassland N2O flux under warming conditions remains unclear in alpine meadow ecosystems. We conducted a long-term manipulative warming experiment in a natural alpine meadow and a cultivated grassland on the Qinghai-Tibetan Plateau to explore the separate and interactive effects of warming and reclamation on the soil N2O emission flux. N2O fluxes were measured under four treatments including control (CK), warming (W), reclamation (R) and warming under reclamation (WR) from August 2018 to July 2019. Our results indicated that compared to the ambient conditions for the growing and non-growing seasons, soil N2O flux was significantly increased 59.1% and 152.0% by warming and 28.4% and 142.4% by reclamation, respectively. Compared with W, WR significantly increased N2O flux by 18.9% and 81.1% during the growing and non-growing seasons, respectively. Soil moisture was negatively correlated to enzymatic activity and N2O flux. Both warming and reclamation promoted soil nitrification by increasing related enzymatic activities that acted to increase the N2O flux. Reclamation resulted in a greater sensitivity of the activity of ammonia monooxygenase and hydroxylamine oxidoreductase to warming, thus enhancing the effects of warming on increasing the N2O flux. Our results indicated that reclamation can additionally increase the effects of warming on N2O emissions for alpine meadows. Therefore, excessive expansion of arable land should be avoided, and new reclamation sites should be planned scientifically, as warming is expected to intensify in the future .